Reformulação do Projeto de Usabilidade da Ferramenta Lagarto - Chaves, Samir; Trinta, Fernando (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2018)
The development of Location Based Mobile Games (LBMG) is a complex task. To overcome this problem, authoring tools have been proposed aimint at reducing the time and eff ort required to create these applications. One of these tools is LAGARTo, a web authoring application to help non-programmers users to create multiplayer LBMGs with augmented reality features. The first version of LAGARTo presented a usability level below end-users expectations. Therefore, this research proposes a new usability project for the LAGARTo editor to address its current problems. This document presents the results already obtained from a work in progress, with promising results of improvement in the usability of LAGARTo.